Revision and description of three new species of the Palaearctic subgenus Gulanthidium of the wool carder bee genus Anthidium (Apoidea: Megachilidae: Anthidiini) - Kasparek, Max (Zootaxa, 2021)
The subgenus Anthidium (Gulanthidium) is a species-poor group of similar species, which is distributed across the West Palaearctic, from Morocco in the west to central Asia in the east. Due to some incorrect species determinations in the literature, the taxonomic situation remains to be fully understood. The situation is reviewed with reference to a rich, still unpublished resource of material from throughout the range. Anthidium flavissimum sp. nov. is described from Afghanistan, A. preoccipitale sp. nov. from Iran, and A. occidentale sp. nov. from Morocco, based on a combination of colour, structural traits, genital morphology, and morphometry. The subgenus as treated here now comprises six species for which a key is presented. Some of the species are sympatric. Species of the subgenus Gulanthidium are very close to A. (Proanthidium) and it should be further examined as to whether these two subgenera should be better combined in a single subgenus.